Optimizing Overall Equipment Effectiveness (OEE) in the Textile Industry Bangladesh (Esquire Knit Composite Limited): A Mixed-Methods Approach to Manufacturing Efficiency - Sheel, Chandan Chandra; Sheel, Chandan Chandra (My University, 2025)
This study investigates the optimization of Overall Equipment Effectiveness (OEE) within the textile industry of Bangladesh, specifically focusing on Esquire Knit Composite Limited, to address the sector's need for enhanced manufacturing efficiency and sustainability in response to current industry demands. The study merged mixed methods, combining an integrated analysis of OEE based on quantitative assessments with qualitative information. Data was collected using a historical review of performance data, in-depth interviews and specific case studies to determine the primary influencers on OEE. The research identifies critical OEE contributors and evaluates the importance of introducing lean principles and sustainable approaches for better OEE.The research reveals significant OEE deficiencies within the studied context, highlighting substantial opportunities for improvement in manufacturing efficiency at Esquire Knit Composite Limited. The analysis of OEE data and qualitative insights provide a basis for recommending targeted optimization approaches. The investigation extends the existing, rather scarce empirical research on the optimization of OEE in the Bangladeshi textile sector. By integrating quantitative OEE analysis and qualitative lean manufacturing and sustainability insights, the study gives a complete view on how to boost manufacturing efficiency in this critical sector. These findings act as an instructive resource for efforts to improve performance and sustainability of the Bangladeshi textile market.
Keywords: efficiency (properties); manufacturing; production; industry; textiles; machines; textile industry; lean thinking; quality control; upkeep (servicing); fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management